Systemic inflammatory response syndrome and long-term outcome after intracerebral hemorrhage - Hagen, Manuel; Sembill, Jochen; Sprügel, Maximilian; Gerner, Stefan; Madžar, Dominik; Lücking, Hannes; Hölter, Philip; Schwab, Stefan; Huttner, Hagen; Kuramatsu, Joji (Neurology, Neuroimmunology and Neuroinflammation, 2019)
ObjectiveTo investigate whether the systemic inflammatory response syndrome (SIRS) without infection as surrogate of a systemic immune response is associated with poor long-term functional outcome in patients with spontaneous intracerebral hemorrhage (ICH).MethodsWe analyzed consecutive patients with spontaneous ICH from our prospective cohort study (2018-2015). SIRS was defined according to standard criteria: i.e., 2 or more of the following parameters during hospitalization: body temperature <36°C or >38°C, respiratory rate >20 per minute, heart rate >90 per minute, or white blood cell count <4,000/L or >12,000/L in the absence of infection. The primary outcome consisted of the modified Rankin Scale (mRS) at 3 and 12 months investigated by adjusted ordinal shift analyses. Bias and confounding were addressed by propensity score matching and multivariable regression models.ResultsOf 780 patients with ICH, 21.8% (n = 170) developed SIRS during hospitalization. Patients with SIRS showed more severe ICH compared with those without; i.e., larger ICH volumes (18.3 cm3, interquartile range [IQR 4.6-47.2 cm3] vs 7.4 cm3, IQR [2.4-18.6 cm3]; p < 0.01), increased intraventricular hemorrhage (57.6%, n = 98/170 vs 24.8%, n = 79/319; p < 0.01), and poorer neurologic admission status (NIH Stroke Scale score 16, IQR [7-30] vs 6, IQR [3-12]; p < 0.01). ICH severity-adjusted analyses revealed an independent association of SIRS with poorer functional outcome after 3 (OR 1.80, 95% CI [1.08-3.00]; p = 0.025) and 12 months (OR 1.76, 95% CI [1.04-2.96]; p = 0.034). Increased ICH volumes on follow-up imaging (OR 1.38, 95% CI [1.01-1.89]; p = 0.05) and previous liver dysfunction (OR 3.01, 95% CI [1.03-10.19]; p = 0.04) were associated with SIRS.ConclusionsIn patients with ICH, we identified SIRS to be predictive of poorer long-term functional outcome over the entire range of mRS estimates. Clinically relevant associations with SIRS were documented for previous liver dysfunction and hematoma enlargement.
CRIS-Team Scopus Importer:2019-10-29